Assessment of Dosimetric Uncertainties in Liver Stereotactic Body Radiation Therapy using kilo-voltage Cone-Beam CT - Clinto C O; Bindhu B (Iranian Journal of Medical Physics)
Introduction: Liver stereotactic body radiation therapy (SBRT) presents distinct challenges caused by respiratory and gastrointestinal motion. While deep inspiration breath hold (DIBH) reduces respiratory motion, gastrointestinal movement and variability in breath-hold consistency can lead to inaccuracies in tumor localization and sparing of critical organs. This study examines dosimetric uncertainties in liver SBRT with DIBH using kilo-voltage cone-beam computed tomography (kV-CBCT).Material and Methods: In this study, twenty-five liver stereotactic body radiation therapy (SBRT) cases were evaluated retrospectively. All patients underwent treatment with volumetric modulated arc therapy (VMAT) in five fractions. The Varian real-time position management™ (RPM) system was employed for image acquisition and delivery with a 5 mm amplitude interval. Treatment plan verifications were performed using daily CBCT at the treatment isocenter. The Varian SmartAdapt automatic deformable image registration tool was utilized for contour propagation. Different dosimetric parameters, including the planning target volume (PTV) mean dose, maximum dose to the spinal canal, liver 21 Gy sparing volume, maximum dose to luminal organs, and dose received by 10 cc, were compared. Paired t-tests were employed to evaluate significant dosimetric changes with a P-value of less than 0.05 considered statistically significant.Results: Among the 25 patients, the PTV Dmean (mean dose) decreased in all cases, with an average reduction of 2.2% (P<0.001). Random deviations were noted in the 21 Gy sparing volume of the liver (P: 0.374). On average, the maximum dose to the spinal canal decreased by 1.5% (P<0.001), even with target-based matching. The luminal organ's maximum dose and the dose to 10 cc exceeded the planned values by an average of 6% (P<0.001) and 6.9% (P: 0.017), respectively.Conclusion: Dosimetric uncertainties are influenced by liver deformation from respiratory motion and the unpredictable positions of luminal organs. Even with 5mm interval amplitude gating, liver deformation remains significant.